Discussing the Undiscussed: What Ingredients are Missing in Faculty Development Programs? - Dinesh Kumar (Research and Development in Medical Education, 2018)
Background: Faculty development programs are essential for the advancement of faculty competence and organizational vitality. This is a multidimensional, daunting task because it involves transforming early career faculty with newer professional competencies such as educators, researchers and leaders. To get accustomed to these newer roles and responsibilitiesin medical education, faculty development programs must be modified and upgraded over time.However, a number of quintessential themes required for contemporary medical education practices are not routinely being addressed, particularly in medical schools in developing countries. Methodology: This narrative review explores some practical complications in the existing faculty development programs and describes six areas to consider as the field of faculty development moves forward: incorporation of faculty identity, faculty vitality, barriers to faculty mentoring,breaking down silos, missing the grounds of evaluation, and importance of phronesis (that is,good character and good judgment). Conclusion: By exploring frequently encountered challenges in designing and implementing faculty development activities, this article asks medical educators to advance faculty development programs beyond formal activities and situate these in a wider context to aid collaboration between colleagues.